Quality, productivity, occupational health and safety and cost effectiveness of ergonomic improvements in the test workstations of an electronic factory - Yeow, Paul H. P.; Sen, Rabindra Nath (Elsevier Science, 2003)
An ergonomic study was conducted to improve the workstations for electrical tests in a printed circuit assembly (PCA) factory in an industrially developing country (IDC). Subjective assessment and direct observation methods were used on the operators to discover the problems in their workstations. The problems found were: (i) poor workstation design, (ii) mix-up of tested and untested boards, (iii) missing or incorrect test steps, and (iv) unclear pass/fail colour inspection criteria. Ergonomic interventions implemented were: (i) an improved workstation with space for resting arms and the oscilloscope and computer keyboards within easy reach of the operators; (ii) clear segregation of tested and untested boards to prevent mix-up; (iii) retraining of operators by more qualified trainers; and (iv) reference colour samples for more effective recognition of different colours in the projection screen. The results were average savings in yearly rejection cost (of US$574,560), reduction in rejection rate, increase in monthly revenue, improvements in productivity, quality, operators' working conditions and occupational health and safety (OHS) and enhancement in customers' satisfaction. The cost of the interventions was less than US$1100. The interventions implemented were simple and inexpensive but resulted in many benefits.